รอยโรคไลเคนอยด์ในช่องปากที่เกี่ยวข้องกับวัสดุอะมัลกัม : Oral Lichenoid Lesions Associated With Amalgam Restorations - Thanapaisal, Siriwan (Region 3 Medical and Public Health Journal - วารสารวิชาการแพทย์และสาธารณสุข เขตสุขภาพที่ 3, 2017)
ความสัมพันธ์ระหว่างการเกิดรอยโรคไลเคนอยด์ในช่องปากกับวัสดุอะมัลกัม ได้รับการยืนยันจากหลายการศึกษา โดยมักพบรอยโรคไลเคนอยด์ในตำแหน่งที่มีการสัมผัสโดยตรงกับวัสดุบูรณะทางทันตกรรม ซึ่งส่งผลให้เกิดปฏิกิริยาไวเกินอย่างช้ากับเนื้อเยื่อบริเวณที่สัมผัสถูก ส่วนใหญ่พบว่าเกิดจากวัสดุอะมัลกัมรอยโรค และอาการจะดีขึ้นเมื่อกำจัดสาเหตุออกไป รายงานผู้ป่วยหญิง อายุ 33 ปี พบรอยโรคที่กระพุ้งแก้ม ลักษณะเป็นร่างแหสีขาวเช็ดถูไม่ออก ร่วมกับรอยแดงและแผลถลอก ตำแหน่งอยู่ติดและใกล้เคียงกับวัสดุอะมัลกัม ผู้ป่วยมีอาการปวดแสบปวดร้อนในช่องปากโดยเฉพาะเมื่อรับประทานอาหารรสจัด ผู้ป่วยได้รับการตรวจชิ้นเนื้อและทดสอบปฏิกิริยาการแพ้ พบว่าผู้ป่วยแพ้นิกเกิลซัลเฟต โคบอลต์คลอไรด์ และฟรากรานซ์มิกซ์ทู จึงทำการรักษาด้วยยาฟลูโอซิโลนอะเซทโทไนด์ชนิดขี้ผึ้ง ความเข้มข้น ร้อยละ 0.1 และทำการเปลี่ยนวัสดุอุดฟันจากวัสดุอะมัลกัม เป็นเรซินคอมโพสิต พบว่ารอยโรคดีขึ้น อาการปวดแสบปวดร้อนหายไปในสัปดาห์ที่ 6 รอยโรคในช่องปากหายไปเกือบหมดในสัปดาห์ที่ 10 และได้ติดตามผลการรักษาเป็นเวลา 6 เดือนไม่พบรอยโรคปรากฏขึ้นอีก คำสำคัญ : รอยโรคไลเคนอยด์ในช่องปาก, วัสดุอะมัลกัม, การทดสอบปฏิกิริยาการแพ้ Abstract The pathogenic relationship between the oral lichenoid lesion(OLL) and amalgam restoration has been confirmed by many studies. An OLL affecting oral mucosa indirect contact with dental restorative materials especially amalgam, represents allergic to reaction. These allergens cause a delayed-hypersensitivity. The lesions are improved after removing the canses. This paper reported a case of A33 year-old female with a chief complaint of burning sensation in her mouth. The symptom was aggravated by spicy food. The oral manifestation revealed white reticular lesions that could not rubbed off with erythematous and ulcerative area, located on both buccalmucosa. The lesions were localized in direct and closed contact to amalgam restoration. Tissue biopsy and skin patch test were worked out. The result of patch test revealed positive reaction to nickel sulfate, cobalt chloride and fragrance mix 2.The patient was treated with 0.1% Fluocinoloneacetonide in orabase and the replacement of amalgam restoration with resin composite. Six weeks after treatment the lesions were improved. The patient was no longer complaining about burning sensation. Ten weeks after treatment the lesions were nearly completely healed. Since six months follow-up, no recurrence has been observed. Key word : oral lichenoid lesion, amalgam, patch test